Keterampilan Guru Kelas dalam Pembelajaran Tematik pada Masa Pandemi di Kelas IV Sekolah Dasar - Marisa, Heni; Mardiah, Mardiah (Mitra PGMI: Jurnal Kependidikan MI, 2022)
This study aims to describe the skills of classroom teachers in thematic learning during the pandemic and find out the barriers to the skills of classroom teachers in thematic learning during the pandemic. This research is qualitative research, the subject of this research is the fourth-grade teacher and two female students, and the object of the research is the skills of the classroom teacher in thematic learning during the pandemic. Data collection techniques used in this study were observation, interviews, and documentation. Furthermore, the data that has been collected is analyzed by reducing the data, presenting the data, and drawing conclusions. Based on the results of the study, it can be concluded that the results of the observations are classified as "good enough" because the answers are at 43%, which is in the 41%-60% interval. This can be seen from several indicators, namely teachers are able to understand the character of students, are able to utilize educational technology, are able to evaluate student learning outcomes. The obstacles in the skills of classroom teachers are the educational background of the teacher, the lack of guidance and training and educational infrastructure.